OP0141-HPR Modifiable Lifestyle Factors Negatively Impact Treating to Target and HAQ Scores in Early Rheumatoid Arthritis Patients. (9th June 2015) - Harrison, T.; Martin, L.
Abstract : Background: Current research suggests that overweight and obese patients with early rheumatoid arthritis (ERA) have higher HAQ scores, and are less likely to achieve remission or low disease activity (LDA). It has also been shown that excess body weight may increase disease severity and that smoking is associated with a worse disease prognosis in these patients. A review of our ERA patients found that they had twice the rate of smoking, and obesity of the general Canadian population. Objectives: To describe and compare DAS28 and HAQ scores between patients with normal BMI's and increased BMI's, and smoking and non-smoking patients in our ERA cohort after 12 months of treatment. Methods: All patients who attended our EIA between 01/2009 and 12/2012 were included in this study. The study was approved by the University of Calgary Conjoint Health Research Ethics Board. Patients are referred to our clinic through a Central Triage system for assessment of new onset of symptoms suggestive of polyarthritis. Patients are reviewed every 3 months for the first year, and are treated to a low disease activity target. A standardized data collection protocol captures clinical data at baseline, 6, and 12 month visits. Variables recorded include demographics, smoking history, World Health Organization (WHO) body mass index (BMI), medications, disease activity (DAS28-ESR) and HAQ scores. Results: There were 150 patients diagnosed with RA included in the study (62% female, 89% Caucasian, mean age 52 years), with 91% meeting 1987 ACR criteria and 96% meeting 2010 ACR/EULAR criteria for RA. The entire cohort had a mean baseline DAS28 score of 5.16 and HAQ 1.18. After 12 months of treatment, DAS28 and HAQ scores were 2.99 and 0.55 respectively. When we reviewed the 12-month DAS28 and HAQ scores for patients with an increased WHO BMI category, we found a mean baseline DAS28 of 5.24 and HAQ of 1.22. After 12 months, scores were 3.21 and 0.656 respectively. Of those patients with increased BMI's, 43% were in remission and 56% achieved a DAS<3.2 (inclusive of remission). Of those patients with normal BMI's, 61.3% were in remission and 64.3% achieved a DAS<3.2 (inclusive of remission). 69% of increased BMI's had HAQ≥1.00, where as only 19% of normal BMI's had HAQ≥1.00 at 12 months. Of patients who smoke, 41% were in remission and 46% achieved a DAS<3.2 (inclusive of remission). Of non-smoking patients, 48% were in remission and 68% achieved a DAS<3.2 (inclusive of remission). 46% of smokers had HAQ≥1.00, while only 16% of non-smokers had HAQ≥1.00. Fisher's exact test was used to determine relationships of these factors at 12 months; no statistically significant relationships could be found except for smoking and HAQ (p=0.00453). Subtle significance was found for the relationship between smoking and LDA (p=0.0419). Conclusions: This study showed that ERA patients followed in our EIA clinic are generally well managed as evidenced by their mean DAS28 and HAQ scores at 12 months. However, when investigating change in these scores specific to patients who smoke and have increased BMI's, a noticeable difference in improvement is evident. Given these observations, further research on a larger ERA cohort may be worthwhile in order to determine clinical and statistical significance. Disclosure of Interest: None declared